The value of cardiopulmonary exercise testing in individuals with apparently asymptomatic severe aortic stenosis: A pilot study - Levy, Franck; Fayad, Nader; Jeu, Antoine; Choquet, Dominique; Szymanski, Catherine; Malaquin, Dorothée; Peltier, Marcel; Tribouilloy, Christophe (Archives of cardiovascular diseases, 2014)
Risk stratification in asymptomatic patients with severe aortic stenosis (AS) is based on exercise test results. However, differentiating between pathological and physiological breathlessness during exercise is sometimes challenging. Cardiopulmonary exercise testing (CPET) may improve quantification of cardiopulmonary exercise capacity in patients with valve diseases. To assess the ability of CPET to detect abnormal responses to exercise and a clinical endpoint (occurrence of European Society of Cardiology guidelines surgical class I triggers). Forty-three consecutive patients (mean age 69±13 years; 31 men) with no reported symptoms and severe AS (aortic valve surface area<1cm2 or indexed aortic valve surface area ≤0.6cm2/m2) prospectively underwent symptom-limited CPET. Twelve (28%) patients had an abnormal exercise test (AET) with symptoms (abnormal dyspnoea n=11; angina n=1). Both VE/VCO2 slope>34 (hazard ratio [HR]=5.76, 95% confidence interval [CI] 1.086–30.587; P=0.04) and peak VO2≤14mL/kg/min (HR 6.01, 95% CI 1.153–31.275; P=0.03) were independently associated with an AET. Furthermore, VE/VCO2 slope>34 (HR 3.681, 95% CI 1.318–10.286; P=0.013) and peak VO2≤14mL/kg/min (HR 3.058, 95% CI 1.074–8.713; P=0.036) were independent predictors of reaching the clinical endpoint. Cardiopulmonary exercise testing is a useful tool for characterizing breathlessness during an exercise test in apparently asymptomatic patients with AS. Peak VO2≤14mL/kg/min and VE/VCO2 slope>34 were associated with an AET and the occurrence of European Society of Cardiology guideline surgical class I triggers. L’épreuve d’effort en cas de sténose aortique serrée asymptomatique d’après l’interrogatoire vise à démasquer la survenue de symptômes. Néanmoins, il est parfois difficile de différentier un essoufflement à l’effort pathologique d’un essoufflement physiologique. Évaluer la capacité de l’épreuve d’effort cardiorespiratoire chez les patients atteints d’une sténose aortique serrée asymptomatique d’après l’interrogatoire à (i) détecter une réponse anormale à l’effort, (ii) à prédire un objectif clinique (la survenue d’une indication opératoire de classe I selon la Société européenne de cardiologie). Une épreuve d’effort cardiorespiratoire a été réalisée prospectivement chez quarante-trois patients consécutifs (d’âge moyen 69±13ans ; 32 hommes) porteurs d’une sténose aortique serrée (surface aortique<1 cm2 ou surface aortique indexée≤0,6 cm2/m2) sans symptôme rapporté à l’interrogatoire. Douze patients (28 %) ont présenté des symptômes lors du test d’effort (dyspnée anormale n=11 ; angor n=1). Une pente VE/VCO2>34 (hazard ratio [HR] 5,76, 95 % intervalle de confiance [IC] 1,086–30,587 ; p=0,04) et un pic de VO2≤14mL/kg/min (HR 6,01, 95 % IC 1,153–31,275 ; p=0,03) étaient indépendamment associés avec la survenue de symptômes lors de l’épreuve d’effort. De plus, une pente VE/VCO2>34 (HR 3,681, 95 % IC 1,318–10,286 ; p=0,013) et un pic de VO2≤14mL/kg/min (HR 3,058, 95 % IC 1,074–8,713 ; p=0,036) étaient associés à une indication chirurgicale de classe I. L’épreuve d’effort cardiorespiratoire peut s’avérer utile pour définir le caractère pathologique d’une dyspnée lors d’un test d’effort dans le cadre d’une sténose aortique serrée censée être asymptomatique selon l’interrogatoire. Un pic de VO2≤14mL/kg/min et une pente VE/VCO2>34 sont associés à la survenue de symptôme lors du test d’effort et à une indication chirurgicale de classe I de l’ESC.